2004
DOI: 10.1097/01.meg.0000108327.52416.c3
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease is the most common cause of chronic diarrhoea in Iran

Abstract: CD is the most common cause of adult chronic non-bloody diarrhoea in Tehran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
2
6
0
1
Order By: Relevance
“…In Iran, Lebanon, Iraq, Saudi Arabia and Kuwait, CD has been reported to be one of the most common causes of chronic diarrhea. [14][15][16] This is almost similar to our findings. The second common symptom was weight loss (14%).…”
Section: Discussionsupporting
confidence: 91%
“…In Iran, Lebanon, Iraq, Saudi Arabia and Kuwait, CD has been reported to be one of the most common causes of chronic diarrhea. [14][15][16] This is almost similar to our findings. The second common symptom was weight loss (14%).…”
Section: Discussionsupporting
confidence: 91%
“…[12] In other studies from northern Iran, a high prevalence of CD was noticed in high-risk groups such as patients with chronic diarrhea and diabetes mellitus. [1920] Although the reported series stated that the prevalence of CD was high in our country, few cases of CD were seen in our daily clinical practice, in spite of using newly developed serological tests such as anti-tTG that are available in most laboratories. Despite the application of simple serological tests in diagnosis of CD, there are few studies from Middle East countries addressing the prevalence of this disease in populations such as those in Syria and Israel.…”
Section: Discussionmentioning
confidence: 97%
“…We found that CD is present in about 9.2% of the patients coming with typical symptoms (12.1% (13/107) of the patients with chronic diarrhea) and 4.0% of those who come with atypical symptoms of malabsorption. Other studies from Iran also reported that CD is the most common cause of chronic nonbloody diarrhea in adults and children, ranging from 6.5% to 19% [15, 16]. These results indicate that classic presentation of malabsorption, specially with chronic diarrhea, is the main presentation of CD in our society.…”
Section: Discussionmentioning
confidence: 64%